CFO-CEO INFORMAL TIES, BUSINESS STRATEGY, AND TAX AGGRESSIVENESS - Khuluqy, Hilmi; Maisaroh, Siti; Rahmiati, Alfa; Tjaraka, Heru (UI Scholars Hub, 2024)
This study aims to provide empirical evidence on the impact of the informal relationship between the CFO and CEO on tax aggressiveness, and the moderating role of business strategy in this relationship. The data used in this study is sourced from companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. The informal relationship between the CFO and CEO is measured through social ties and CFO co-option, while tax aggressiveness is measured by book-tax differences. This study also explores how business strategies, categorized as prospector or defender, moderate this relationship. The results indicate that CFO-CEO social ties significantly reduced tax aggressiveness. However, the findings did not support the moderating role of either prospector or defender business strategies in strengthening or weakening this relationship. The implications of these results are relevant for managerial decision-making and academic literature, and suggest directions for future research that consider broader internal and external company dynamics.